Islamic Educational Psychology: The Urgency In Islamic Religious Education Learning - Mahfud Heru Fatoni; Siti Rohimah; Baron Santoso; Hamid Syarifuddin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to reveal the important role of Islamic educational psychology in the Islamic Religious Education learning process. The method used is library research which involves collecting information and data by utilizing various materials available in the library, such as reference books, articles, journals and other relevant documents related to the topic being researched. From the research results, it is concluded that Islamic educational psychology plays an important role in learning Islamic religious education because of the interactive dynamics between teachers and students during the learning process. Without the knowledge of Islamic educational psychology in every learning process, it is certain that learning objectives will not be achieved optimally and the learning process will be ineffective. Furthermore, Islamic religious education involves instilling and strengthening the principles of faith which serve as a spiritual basis. A person's entire being is shaped by the teachings of the Islamic religion, and every attitude and behavior is influenced by his faith.